O Irã nuclear - Germer, André; Taguchi, Américo Kunio; Rocha, Guy Hermínio; Chalella Júnior, João; Silva, Jorge Luiz da; Rezende, Nilton Gonçalves (Coleção Meira Mattos: revista das ciências militares, 2010)
Resumo não disponível